The impact of freedom on fertility decline. Issue 1 (7th January 2013) - Campbell, Martha M; Prata, Ndola; Potts, Malcolm
Abstract : Although fertility decline often correlates with improvements in socioeconomic conditions, many demographers have found flaws in demographic transition theories that depend on changes in distal factors such as increased wealth or education. Human beings worldwide engage in sexual intercourse much more frequently than is needed to conceive the number of children they want, and for women who do not have access to the information and means they need to separate sex from childbearing, the default position is a large family. In many societies, male patriarchal drives to control female reproduction give rise to unnecessary medical rules constraining family planning (including safe abortion) or justifying child marriage. Widespread misinformation about contraception makes women afraid to adopt modern family planning. The barriers to family planning can be so deeply infused that for many women the idea of managing their fertility is not considered an option. Conversely, there is evidence that once family planning is introduced into a society, then it is normal consumer behaviour for individuals to welcome a new technology they had not wanted until it became realistically available. We contend that in societies free from child marriage, wherever women have access to a range of contraceptive methods, along with correct information and backed up by safe abortion, family size will always fall. Education and wealth can make the adoption of family planning easier, but they are not prerequisites for fertility decline. By contrast, access to family planning itself can accelerate economic development and the spread of education.